2003
DOI: 10.1002/hipo.10063
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐induced memory impairment in trace fear conditioning: A hippocampus‐specific effect

Abstract: It has been hypothesized that the amnesic effects of alcohol are through selective disruption of hippocampal function. Delay and trace fear conditioning are useful paradigms to investigate hippocampal-dependent and independent forms of memory. With delay fear conditioning, learning of explicit cues does not depend on normal hippocampal function, whereas learning explicit cues in trace fear conditioning does. In both delay and trace fear conditioning, the hippocampus is involved in learning to contextual cues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 70 publications
(95 reference statements)
7
48
0
Order By: Relevance
“…105 This memory impairment may reflect a disruption of encoding, storage, consolidation, and/or retrieval capability. 106,107 Other studies have shown that moderate doses of ethanol delivered after learning generally enhance or have little effect on memory examined the next day, 108,109 and caffeine at moderate doses has been shown to facilitate memory acquisition and retention in animals assessed on various learning tasks. [110][111][112][113] A few articles have focused on the interaction between caffeine and ethanol on the memory in rodents.…”
Section: Caffeine-ethanol Interactions: Effects On Learning and Memorymentioning
confidence: 99%
“…105 This memory impairment may reflect a disruption of encoding, storage, consolidation, and/or retrieval capability. 106,107 Other studies have shown that moderate doses of ethanol delivered after learning generally enhance or have little effect on memory examined the next day, 108,109 and caffeine at moderate doses has been shown to facilitate memory acquisition and retention in animals assessed on various learning tasks. [110][111][112][113] A few articles have focused on the interaction between caffeine and ethanol on the memory in rodents.…”
Section: Caffeine-ethanol Interactions: Effects On Learning and Memorymentioning
confidence: 99%
“…Many studies have used short trace intervals ranging from 1 to 2.5 sec (Crestani et al 2002;Holmes et al 2002;Kinney et al 2002;Wrenn et al 2002), but evidence suggests that intervals this short do not engage the hippocampus and may therefore be more similar to delay fear conditioning, in which there is no interval between CS and US presentation (Chowdhury et al 2005;Misane et al 2005;Wanisch et al 2005). Still others have used longer trace intervals ranging from 20 to 30 sec (Huerta et al 2000;Weitemier and Ryabinin 2003;Gould et al 2004;Yee et al 2004;Wiltgen et al 2005). We chose an 18-sec trace interval because studies that have examined the role of the hippocampus in trace fear conditioning at multiple interval lengths (1-60 sec) have reported that a 15-20 sec interval is most effective at engaging the hippocampus (Chowdhury et al 2005;Misane et al 2005;Wanisch et al 2005).…”
Section: Org Downloaded Frommentioning
confidence: 99%
“…Delay fear conditioning, measured by using fear-potentiated startle, is also expressed maximally at a time point that is coincident with ISI (Davis et al 1989). In contrast, by using heart-rate or freezing as a measure of conditioning, fear has been observed to persist, and even on occasion to peak, after CS offset in delay and in trace conditioning (Quinn et al 2002;McEchron et al 2003;Weitemier and Ryabinin 2003), even though the hippocampus appears to encode the CS-US interval (McEchron et al 2003). This difference between freezing and fear-potentiated startle could be at least in part attributable to differences in sensitivity of the two behavioral measures to contextual fear.…”
Section: Learning and Memory 209mentioning
confidence: 99%